The Euro-dividend: public debt and interest rates in the Monetary Union - Luigi Marattin; Simone Salotti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2010)
The ongoing massive fiscal policy stimulus triggered increasing concerns on the potential impact on interest rate levels, as economic theory predicts. Particularly, the deterioration of some EMU countries' fiscal positions has been putting at risk Eurozone' financial stability. In this paper, we estimate a Panel VAR (PVAR) model on the EMU area employing annual data from 1970 to 2008 in order to assess the qualitative and quantitative impact of public debt on interest rates Our results show that prior to the introduction of the Euro an increase in public debt led to positive and significant effect on long-term nominal interest rates, with a stronger effect for high-debt countries. After the introduction of the single currency, the effect vanishes (in line with Bernoth 2004). We interpret this result as a confirmation of the crucial role of the monetary union in weakening the automatic risk-premium-based channel between debt shocks and returns on government bond.
Keywords: E62; G12; 330